Global developments in central bank digital currency - Ozili, Peterson K. (IGI Global, 2024)
In an era defined by rapid technological advancement, the nature of money finds itself at a crossroads, presenting both opportunities and challenges for global financial systems. The rise of Central Bank Digital Currencies (CBDCs) stands as a testament to this paradigm shift, offering the promise of efficiency, transparency, and financial inclusion. However, amidst the burgeoning interest in CBDCs, a pressing problem emerges: the lack of comprehensive understanding and insight into their development on a global scale.Recognizing this critical gap, Global Developments in Central Bank Digital Currency emerges as a guide for clarity in the complex landscape of monetary evolution. By synthesizing insights from diverse regions and jurisdictions, this book offers a holistic view of CBDC initiatives, unraveling the intricate web of motivations, challenges, and implications. From Africa to Asia, from Europe to Oceania, the book delves into country-specific developments, shedding light on the role of politics, culture, and informal institutions in shaping CBDC adoption.